-2lx-1l+10=-4

Simple and best practice solution for -2lx-1l+10=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2lx-1l+10=-4 equation:


Simplifying
-2lx + -1l + 10 = -4

Reorder the terms:
10 + -1l + -2lx = -4

Solving
10 + -1l + -2lx = -4

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -1l + -10 + -2lx = -4 + -10

Reorder the terms:
10 + -10 + -1l + -2lx = -4 + -10

Combine like terms: 10 + -10 = 0
0 + -1l + -2lx = -4 + -10
-1l + -2lx = -4 + -10

Combine like terms: -4 + -10 = -14
-1l + -2lx = -14

Reorder the terms:
14 + -1l + -2lx = -14 + 14

Combine like terms: -14 + 14 = 0
14 + -1l + -2lx = 0

The solution to this equation could not be determined.

See similar equations:

| 57+x+x-24=180 | | 3b-7(3+b)=b+3 | | x+3x+x-4=76 | | 18+8y=7-3y | | 3x-7=11+5x | | 2x+48+x=180 | | 5y+4=4y-8 | | 200=6x^2+8xh | | =6x^2+8xh | | -9+4x=-85 | | 82+x+x=180 | | A=6x^2+8xh | | w(w+3)=28 | | -9(2b+4)+(19b-6)=0 | | 2-0.5(f-9)=0.8(f-9) | | 16-5(3t-4)=8(-2t+12) | | -2(x+3)=4x+3 | | 8x-3y=24-5y | | 0.20(24)-0.05x=0.10(24+x) | | x(x+4)+x(x+2)=2x+12 | | 0.3(n-18)=0.9n | | 0.7y-0.5y=6.6 | | 3.4x+4=2.4x | | x+5*-8=0 | | -2x+1=27 | | 2-I/2+5i=0 | | 33+15=3w-w+4w | | -116-6g=-32 | | 8-2x=2c | | 6z=17 | | 5y+35=0 | | 6x^2-32x+32=0 |

Equations solver categories